PENGARUH BUBUK DAUN KETAPANG (Terminalia catappa) TERHADAP PERFORMA PERTUMBUHAN IKAN GUPPY (Poecilia reticulata) - Andre Rachmat Scabra; Sofhia Dewi Arini; Muhammad Junaidi (Universitas Teuku Umar, 2022)
Indonesia has biodiversity and one of which is the diversity of ornamental fish species both marine and freshwater. One type of freshwater ornamental fish is quite in demand, namely guppies. This study aimed to analyze the effect of adding tropical almond leaf powder to the growth performance of guppies. This study used an experimental method with the addition of tropical almond leaf powder. The experimental design used was a completely randomized design (CRD) consisting of 5 treatments, namely treatment A (without the addition of tropical almond leaf powder/control), B (tropical almond leaf powder with a dose 0,13 g/L), C (tropical almond leaf powder with a dose 0,26 g/L), D (tropical almond leaf powder with a dose 0,40 g/L), E (tropical almond leaf powder with a dose 0,53 g/L), and each treatment was repeated 3 times. The data were analyzed using analysis of variance (ANOVA) at a significant level of 5% with a 95% confidence interval and continued with the Duncan test. The result showed that the addition of tropical almond leaf powder had a significant effect on the parameters of absolute weight growth, specific weight growth rate, absolute length growth, specific length growth rate, feed conversion ratio, bacterial abundance and oxygen consumption level. Yet, it did not have a significant effect on the parameters of the survival rate of guppies. The best dose of tropical almond leaf powder obtained in this study was in treatment C (0,26 g/L).Keywords: Growth Performance, Guppies, Tropical Almond.